WAYS TO IMPROVE TAXATION OF PROPERTY INCOME OF NATURAL PERSONS - Нарманов Эркин Абдуалимович (Web of Journals Publishing, 2024)
In the thesis, the reforms implemented in the development of business activity, natural persons engaged in business activity and the mechanisms of their taxation were studied, suggestions were made regarding the further improvement of the current procedure of property income taxation and the introduction of new mechanisms for increasing the property income of individuals.
Keywords: property, property income, natural person, property income, dividend, object, base, tax rates, tax amount.